Policy Measures for the Diaspora during the COVID-19 Crisis: The Case of Cyprus - Konstantinidou, Angeliki; Vintila, Daniela (HAPSc Policy Briefs Series, 2020)
The COVID-19 pandemic constitutes an unprecedented challenge for policy-makers worldwide. The coronavirus outbreak has rapidly put into question states’ preparedness for crisis management, while also raising particular concerns on how national governments assist their citizens abroad in situation of distress. This Policy Brief tackles the issue of governmental responsiveness to the diaspora in a context of pandemic alert. In doing so, we focus on the case of Cyprus, one of the EU Member States with the largest share of citizens residing abroad. Drawing on official documents publicly released by different Cypriot authorities, we map the different initiatives adopted by the Cypriot Government in the attempt to assist its diaspora during the pandemic. Our analysis shows that, in line with its traditional approach towards non-residents citizens, Cyprus has adopted a rather pro-active stance vis-à-vis its population abroad. Since the COVID-19 outbreak, several initiatives have been put forward by ministerial actors, often via inter-institutional cooperation, aiming to mobilise resources that could meet diaspora’ needs. However, the Government’s engagement with the diaspora during this crisis has remained rather selective. Most policy measures primarily aimed to provide support to Cypriots in specific (mainly European) destination countries, while also targeting particularly vulnerable groups of individuals stuck abroad during the pandemic.